ANALYSIS OF TEACHER’S STRATEGY IN TEACHING SPEAKING SKILLS TO STUDENTS AT MA MODERN NURUL-AMIN - Mukhlisin; Muhammad Yassin; Dewi Ismu Purwaningsih (Universitas Al-Qolam Malang, 2024)
English is an imperative skill to understand because it has a dominant part in almost the current field in globalization contexts such as in media, technology, science, business, and education. This study was conducted to know the strategies were used by the teacher in teaching speaking skills to students at MA Modern Nurul-Amin Kubu Padi. The subjects of this research were students and the English teacher at MA Modern Nurul-Amin. In conducting the research, the researcher constructs a descriptive qualitative approach. Then, the data were collected through observation checklist, field note and interviews, as well as by questionnaires. The observation checklist and field note were conducted at MA Modern Nurul-Amin during the learning process. Meanwhile, the interviews were conducted with students and the English teacher. Additionally, the questionnaires were distributed to students and the English teacher as the additional or a proponent data of the research. Then, the data were analyzed qualitatively. The findings showed that there were several strategies used by teacher in teaching English speaking skills, the strategies were debate, speech, English class conversation, role play, and group discussion. Moreover, the mostly strategies used by teacher was debate, speech, English class conversation, and group discussion in different level. Keywords : Teacher’s Strategy, Students’ Speaking Skills, Analysis of Teaching